2018
DOI: 10.1186/s40538-018-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Exclosures backed up with community-based soil and water conservation practices increased soil organic carbon stock and microbial biomass carbon distribution, in the northern highlands of Ethiopia

Abstract: Background: Land degradation is a treat for natural resources in Tigray high lands of northern Ethiopia, where 30-50 percent of the soil productive capacity has been lost in the past 500 years. Restoration and management of degraded lands improve soil health through enhancing soil organic carbon (SOC) stock and microbial biomass carbon (MBC). The knowledge on SOC and MBC concentration and distribution is essential to refine soil management, thereby restoring the ecosystem. This paper quantified the effect of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The assessment indicated that removal of residues, total harvest, and leaching losses accounted for the major causes of nutrient losses under permanent and vegetable cropping while erosion accounted for the major causes of nutrient losses in under cereals and other annuals. Welemariam et al (2018) assessed the impact of exclosures and soil and water conservation (SWC) practices on SOC concentration, SOC stock, and microbial biomass carbon in the highlands of northern Ethiopia. They reported that exclosures with terraces gave the highest SOC stock (29 Mg/ha) followed by exclosures only (24 Mg/ha), terraces (21 Mg/ha), and non-conserved grazing lands (16 Mg/ha).…”
Section: Past and Present Scientific Evidence Of Soil Organic Carbon mentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment indicated that removal of residues, total harvest, and leaching losses accounted for the major causes of nutrient losses under permanent and vegetable cropping while erosion accounted for the major causes of nutrient losses in under cereals and other annuals. Welemariam et al (2018) assessed the impact of exclosures and soil and water conservation (SWC) practices on SOC concentration, SOC stock, and microbial biomass carbon in the highlands of northern Ethiopia. They reported that exclosures with terraces gave the highest SOC stock (29 Mg/ha) followed by exclosures only (24 Mg/ha), terraces (21 Mg/ha), and non-conserved grazing lands (16 Mg/ha).…”
Section: Past and Present Scientific Evidence Of Soil Organic Carbon mentioning
confidence: 99%
“…In Ethiopia, significant increase in SOC and improvement of ecosystem services has been achieved through the conversion of open grazing lands to exclosures (protected areas with zero grazing and prohibition of human activities) across different agro-ecological zones (Descheemaeker et al 2006a(Descheemaeker et al , 2006bCorral-Nuñez et al 2014;Assefa et al 2017;Welemariam et al 2018). For example, Corral-Nuñez et al 2014 studied the current and predicted SOM in northern Ethiopia and reported significant recovery of SOM ranging from 2.6 to 5.6% in exclosure after 20 years compared to 2.1% to 2.9% in cropland.…”
Section: Options For Increasing Soil Organic Carbon Stock In Ethiopiamentioning
confidence: 99%
See 1 more Smart Citation
“…Soil carbon change can happen in response to a broad range of environmental and management factors [73]. Livestock grazing is a vitally common issue that affects plant growth, plant species diversity, and soil carbon accumulation [74]. In 2010, between one-third and a half of the entire world's agricultural land was in a degraded condition, and a fifth was considered severely degraded.…”
Section: Overgrazingmentioning
confidence: 99%
“…Studies conducted by authors [6][7][8][9][10][11][12] have shown the positive role of conversion of grazing lands to exclosures on restoration of soils that were previously degraded in the region. However, most of these studies focused in the mid (1500-2300 m above sea level) and highlands (> 2300 m above sea level) with limited focus to the lowlands (< 1500 m above sea level) such as the study area, Tselemti district.…”
Section: Introductionmentioning
confidence: 99%